Zur Inschrift des Primus Pilus G. Baienius Ianuarius aus Novae - Piso , Ioan (Studia Europaea Gnesnensia, 2017)
Among the numerous inscriptions from Novae published by the Polish colleagues, that of G. Baienius Ianuarius deserves a special attention. It has been raised on October the 5th 227 AD under the governorship of Lucius Mantennius Sabinus. On the left side of the basis a text in hexameters contains the military carrier of C. Baienius Ianuarius. It is the lecture of this text that the author tries to improve. One of the conclusions is that G. Baienius Ianuarius carried out as a centurio of the legio I Italica a mission in Rome about 223/224 AD. Another conclusion is that the statue represented an aquila, symbol of the legion